Seroprevalence of Hepatitis C Virus in HIV/AIDS Patients in Jos, Nigeria (Bangladesh Liver Journal, 2009)
Introduction: Hepatitis C Virus (HCV) infection is a life threatening infection and is more serious in people living with HIV/AIDS (PLWHA). It leads to liver damage more quickly and may also affect the treatment of HIV infection. This study was aimed at determining the seroprevalence of HCV, possible risk factors for HCV infection and highlighting the importance of HCV screening in PLWHA in Jos, Nigeria. Materials and Methods: One hundred and eighty two blood samples were collected from confirmed HIVpositive patients attending clinics at the Faith Alive Hospital in Jos for the detection of anti-hepatitis C antibodies. An enzyme linked immunosorbent assay (ELISA), DIALABTM HCV Ab test kit (DIALAB GmbH, Australia) was used for the analysis. Results: Sixty one of the 182 samples tested positive giving a co-infection rate of 33.9%. Old age and low educational levels of the patients were found to be associated with HCV/HIV co-infection (P